Droplet-Based Microfluidic System for Tumor Cell Encapsulation in Alginate Beads and Anticancer Drug Testing - Yu, Linfen; Cheung, Karen C. (CMBES Proceedings, 2010)
Three-dimensional cell culture is critical in characterizing anticancer treatments since it may provide a better model than monolayer culture of in vivo tumor cells. Moreover, continuous dynamic perfusion allows the establishment of long term cell culture and drug interaction to exposed tumor spheroids. Here we present a droplet-based microfluidic system for formation of uniform alginate gel beads, trapping alginate beads in microsieve structures, and characterization of the interaction between tumor spheroids and anticancer drug, all in one integrated platform. In our microfluidic device, breast cancer cells were used as a model system to validate the platform. After the tumor spheroid formation, serial concentrations of drugs were used to investigate the dose-effect relationship between drug and cell proliferation and cell death. After the cells were treated with drug for 2 days, the cells were stained with live/dead fluorescent dye and detected with confocal microscopy. Compared with that of the monolayer culture cells, small tumor spheroids have higher resistance to anticancer drugs than monolayer culture cells which is valuable for identifying correct clinical dosing. This microfluidic platform requires minimal culture reagents and mechanical labor which will significantly reduce the cost and time and realize the high throughput cell cytotoxicity assessment. In future it may replace labour intensive, microtiter-plate based screening platforms currently implemented in the laboratory.